Does the effect of aquatic plant types on invertebrate assemblages change across seasons in a subtropical wetland? - Gallardo, Luciana Irene (2017)
Fil: Gallardo, Luciana Irene. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro de Ecología Aplicada del Litoral; Argentina.